Economics of Community-Based Disaster Management and Household Participation: Evidence of The Western Nepal - Bista, Raghu Bir (ARRUS Journal of Social Sciences and Humanities, 2022)
This paper examines households' participation in community-based disaster management in western Nepal based on the secondary and primary data sets under the framework of explorative and descriptive statistics. As a result of the study, multi-hazards occurred. Out of these multi-hazards, the catchment areas and the community were disaster-prone by flood and landslide more than other hazards: insects, drought, animals, etc. in terms of severity and frequency. Further, the community-based disaster management that was proactive and participatory to assess disasters, hazard locations, and their impacts made stakeholders to the community for their participation, ownership, and resilience. In community-based disaster management, the household was actively participatory not only in pre-disaster, disaster, and post-disaster focusing on preparedness and planning more than rescue and reconstruction, rehabilitation, and recovery. Its economic cost is 78 mean days per household. It is 21 percent of a year (365 days) calendar. Its mean wage income loss is 39000 Nepali Rupees (330 USD) per annum that is 30 percent of 1071 USD per capita. Thus, the rural household has a significant economic cost of CBDMG activity to be resilient from multi natural hazards. However, it can reduce multi times the disastrous cost to them. Its outcome may not be positive to household income, welfare, and poverty reduction. Thus, the community-based disaster management approach is effective was in terms of less time, fewer resources but the quick response.